2007
DOI: 10.1097/01.tp.0000286172.57076.df
|View full text |Cite
|
Sign up to set email alerts
|

Early Hematopoietic Microchimerism Predicts Clinical Outcome After Kidney Transplantation

Abstract: Microchimerism was frequent after kidney transplantation and correlated with a significantly lower incidence of rejection. We propose that early microchimerism monitoring could help early detection of low rejection-risk recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…As we previously published (46), we believe that to include molecular detection of microchimerism as a routine protocol in solid organ transplanted recipients can provide undeniable additional data, involving clinical decisions, ultimately concerning the fate of the transplanted organ. …”
Section: Discussionmentioning
confidence: 92%
“…As we previously published (46), we believe that to include molecular detection of microchimerism as a routine protocol in solid organ transplanted recipients can provide undeniable additional data, involving clinical decisions, ultimately concerning the fate of the transplanted organ. …”
Section: Discussionmentioning
confidence: 92%
“…Some reports show that microchimerism is associated with graft acceptance 13 and that it correlates with lower incidence of rejection. 14,15 Other investigators, however, do not confirm a beneficial effect of microchimerism on graft acceptance. [16][17][18] Endothelial cell chimerism after renal transplantation, resulting from the replacement of donor endothelial cells with cells from the recipient, is mainly observed in grafts of patients who have experienced rejection.…”
Section: Introductionmentioning
confidence: 99%
“…In one of those studies, transplant recipients, who displayed microchimerism at 2 mo after graft kidney implantation, had a significantly lower incidence of biopsy-proven acute rejection during the subsequent four years compared with patients who were microchimerism-negative. 32 Whereas in a mouse model it was shown that microchimerism was the causal factor in maintaining deletion of donor-specific CD8+ T cells, 33 microchimerism after human transplantation does not seem to be accompanied by diminished anti-donor T cell responses. 31 In a girl who had received a liver allograft from a deceased, unrelated male donor, spontaneous donor chimerism (94-100%) was observed in T, B, and NK cells, and granulocytes at 13 mo post-transplantation.…”
Section: Donor Microchimerism In the Recipientmentioning
confidence: 99%
“…While macrochimeric conditions appear to be related to tolerance mechanisms, the clinical impact of donor microchimerism in solid organ transplantation is less clear. 28 In several studies it was shown that microchimerism in humans is associated with graft acceptance 29,30 and a lower incidence of rejection 31,32 after kidney, liver or small bowel transplantation. In one of those studies, transplant recipients, who displayed microchimerism at 2 mo after graft kidney implantation, had a significantly lower incidence of biopsy-proven acute rejection during the subsequent four years compared with patients who were microchimerism-negative.…”
Section: Donor Microchimerism In the Recipientmentioning
confidence: 99%